Employee Competencies Interrelation of Workforce Agility Attributes (International Journal of Innovative Research in Engineering & Management, 2022)
Organizations must be able to evaluate the  performance of their digital efforts quickly to know where to  channel human resources and when to pull the plug if  necessary. In a demand-based banking services environment  the organization need to build agility and competencies to  adapt to shift and act on it with speed. The workforce  sharpens the behavioral competencies to meet the agility  dimensions is an answerable to stay strong in business  operations. This research is to understand the relationship of  behavioral competencies and workforce agility attributes. It  gives the insight of knowledge on employee behavior at  workplace to find out the research model. Further, empirical results significant that behavioral competencies of  motivation, commitment, analytical reasoning and employee  foresight were found to be strongly associated with  workforce agility attributes of adaptability, developmental  and competent. Moreover, the paper opens up discussion for a strategic managerial implication.
Keywords: Employee Competencies; Workforce Agility; Motivation; Developmental; Adaptability